RANCANG BANGUN APLIKASI PENGELOLAAN SURAT PADA STIKES DR. SOETOMO - Susanto, Tri Rudy; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
STIKES hospital Dr .Soetomo are higher education institutes private health belonging to foundation Dr .Soetomo. Stikes was an improvement status academy recorder medical and informatics health ( APIKES ) a pen husada who get permission the implementation of education since 2003 / 2004. Based on the structure of the organization stikes the foundation of hospital Dr. Soetomo surabaya there are administrasi common and finance ( BAUK ) that have children division that is affairs offices public administration. As for one of the tasks of affairs offices administration common is coordinating and make an agenda the whole process a letter in and a letter out to the or other institutions. Based on the job, there are management process of a letter that had difficulty in manage.This is because the absence of a system ( application ) that can help stikes dr .Soetomo in the management of a letter. Architecture of mail management application on Stikes Dr. Soetomo is an application that there is a need for the office of general administrative work in conducting the management of a letter. With the existence of this application can help with the work the office of general administrative work in managing a letter in and a letter out into institution or other Architecture of mail management application on Stikes Dr .Soetomo is an application that there is a need for the office of general administrative work in conducting the management of a letter. With the existence of this application can help with the work the office of general administrative work in managing a letter in and a letter out into institution or other institutions. After tested, application management of a letter at Stikes Dr.Soetomo be able to manage a letter in accordance with the procedures. So, application it may help in making numbering a letter automatically, disposition to unit of work which is intended, search archive letters and archive storage letter.